Academic content collection. Level B ([United Kingdom] : Thomson Heinle, 2007)
Collection of 6 stories of level B reader for practice and reinforcement
Arctic Melissa Cole -- Photosynthesis Bonnie Juettner -- Anne Frank Kristen Woronoff -- Space travel Melissa Cole -- Alexander Graham Bell Deanne Durrett -- The Oregon trail Dana Meachen Rau
Title from container
Keywords: Bell, Alexander Graham, -- 1847-1922 -- Juvenile literature; Frank, Anne, -- 1929-1945 -- Juvenile literature; Reading; Ecology -- Arctic regions -- Juvenile literature; Photosynthesis -- Juvenile literature; Telephone -- History -- Juvenile literature; Jewish children in the Holocaust -- Netherlands -- Amsterdam -- Biography -- Juvenile literature; Pioneers -- Oregon National Historic Trail -- Juvenile literature; Space flight -- Juvenile literature